Um canto de amor e saudade: O neotrovadorismo na poesia de Vinicius de Moraes - Leite, Jonathan Lucas Moreira (2017)
The present work is in the field of medieval studies, as well as in the field of semiotic studies, and has as its main objective to analyze the resonances of troubadour literature in the poetry of Vinicius de Moraes, a Brazilian poet and composer. Initially, we will make a panoramic study of the work of the author and a survey of his substantial criticism. In the second chapter, we will present the main concepts of the General Theory of Signs, the theoretical-methodological considerations used in our analysis. Posteriorly, we will discuss the main characteristics of the Troubadourism, guided by the medievalists Spina (1956), Martins and Nunes (2014) and Maleval (2002), in addition to the contributions of the poet and essayist Paz (1994). We will also discuss the presence of Neotrovadorismo in Brazilian art, as well as the studies about these updates. Finally, we will analyze the marks of troubadour literature in the poetry of Vinicius de Moraes, based on three aspects: the dialogue between the poems of the author and the songs of the lover, demonstrated in the analysis of the poem Romanza; the recreation of the songs of love in the texts of the poet, analyzed in the Soneto de carta e mensagem; and, finally, we will examine the presence of the remaining symbols of the medieval barcarolles in the poetry of Vinicius de Moraes, from the poems Mar and Marinha.